Modeling Brain Tumors: A Perspective Overview of in vivo and Organoid Models - Antonica, Francesco; Aiello, Giuseppe; Soldano, Alessia; Abballe, Luana; Miele, Evelina; Tiberi, Luca (Frontiers in Molecular Neuroscience, 2022)
Brain tumors are a large and heterogeneous group of neoplasms that affect the central nervous system and include some of the deadliest cancers. Almost all the conventional and new treatments fail to hinder tumoral growth of the most malignant brain tumors. This is due to multiple factors, such as intra-tumor heterogeneity, the microenvironmental properties of the human brain, and the lack of reliable models to test new therapies. Therefore, creating faithful models for each tumor and discovering tailored treatments pose great challenges in the fight against brain cancer. Over the years, different types of models have been generated and, in this review, we investigate the advantages and disadvantages of the models currently used.